Exploring the Potential of Leading Economic Sectors in Rebana Region, West Java Province. - Albanah, Rosa Saefi Yusuf; Athallah, Nadila Ersya (Jurnal Ekonomi Pembangunan, 2024)
The study explores the basic and leading sectors of the Rebana Region as areas of development planning through industrialization that are prepared to accelerate economic development and overcome regional disparities in the West Java Province. The research method used is a quantitative method with a descriptive approach. Data collection was carried out secondarily as Gross Regional Domestic Product (GDRP) data and analyzed using Location Quotient (LQ), Shift-share and Klassen Typology techniques.The results showed potential sectors are mining and careers, agriculture, forestry and fisheries, and corporate services. Progressive and competitive sectors that support the development and acceleration of industrialization are water supply, sewerage, waste management and remediation activities, construction, transportation, and storage, accommodation and food service activities, financial and insurance activity and real estate activity. Furthermore, the fastest-growing sectors are construction, transportation, and trade, as well as financial services and insurance, but the industrial sector falls into the underdeveloped category. Conclusion: This area has great potential to develop. When referring to the plan of economic acceleration through industrialization for the current relatively undeveloped territory, infrastructure construction and investment are carried out in the development of the territory in the hope that industrial sectors and other potential sectors can thrive and be competitive.